3He pO2 mapping is limited by delayed‐ventilation and diffusion in chronic obstructive pulmonary disease. Issue 3 (9th May 2013) - Marshall, Helen; Parra‐Robles, Juan; Deppe, Martin H.; Lipson, David A.; Lawson, Rod; Wild, Jim M.
<x xml:space="preserve">Abstract</x> Purpose Lung pO2 mapping with 3He MRI assumes that the sources of signal decay with time during a breath‐hold are radiofrequency depolarization and oxygen‐dependent T1 relaxation, but the method is sensitive to other sources of spatio‐temporal signal change such as diffusion. The purpose of this work was to assess the use of 3He pO2 mapping in patients with chronic obstructive pulmonary disease. Methods Ten patients with moderate to severe chronic obstructive pulmonary disease were scanned with a 3D single breath‐hold pO2 mapping sequence. Results Images showed signal increasing over time in some lung regions due to delayed ventilation during breath‐hold. Regions of physically unrealistic negative pO2 values were seen in all patients, and regional mean pO2 values of −0.3 bar were measured in the two patients most affected by delayed ventilation (where mean time to signal onset was 3–4 s). Conclusions Movement of gas within the lungs during breath‐hold causes regional changes in signal over time that are not related to oxygen concentration, leading to erroneous pO2 measurements using the linear oxygen‐dependent signal decay model. These spatio‐temporal sources of signal change cannot be reliably separated at present, making pO2 mapping using this methodology unreliable in chronic obstructive pulmonary disease patients with significant bullous emphysema or delayed ventilation. Magn Reson Med 71:1172–1178, 2014. © 2013 Wiley Periodicals, Inc.